KONSEPSI KEBIJAKAN HUKUM DALAM PEMBERIAN DISPENSASI NIKAH TERHADAP MENINGKATNYA ANGKA PERCERAIAN RUMAH TANGGA (Analisis Yuridis Putusan Perkara Nomor 203/Pdt.P/2023/PA.SJJ) - Dewi Nawang Wulan; Danela Mutia Rahma Handayani; Dedy Stansyah (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
This research aims to analyze decision Number 203/Pdt.P/2023/PA.SJJ regarding granting marriage dispensations against the increasing number of household divorces. The research method used is normative juridical with a case approach. Data collection was carried out through literature study. The results of the research show that the granting of marriage dispensation by the Sijunjung Religious Court in decision Number 203/Pdt.P/2023/PA.SJJ was based on the judge's consideration that the Petitioners' petition did not conflict with statutory regulations, customary law, local wisdom, or religion and All decisions have gone through an ongoing legal process involving both families of the prospective bride and groom, both people. However, granting a marriage dispensation must still take into account aspects of the mental, physical and economic readiness of the prospective bride and groom. Apart from that, there needs to be preventive efforts from the government and society to reduce the number of underage marriages and requests for marriage dispensations, so as to reduce the number of household divorces, especially at an early age.